Susceptibility patterns of Candida species collected from intensive care units in Portugal: a prospective study in 2020–2022 - Teresa Nascimento; João Inácio; Daniela Guerreiro; Priscila Diaz; Patrícia Patrício; Luís Proença; Cristina Toscano; Helena Barroso (Infection Prevention in Practice)
Summary: Background: For Candida infections antifungal therapy is often empirical and mainly depends on locally antifungal surveillance data, which differs between geographic regions. Aims: To monitor the epidemiology and antifungal susceptibility of Candida spp. from combined axillar-groin samples in intensive care unit (ICU) patients on admission (day1, D1), day 5 (D5) and day 8 (D8). Methods: From 2020 to 2022, 675 patients from three ICUs were enrolled. Candida isolates were identified by MALDI-TOF MS and PCR. In vitro antifungals susceptibility tests (AFST) were performed for fluconazole, voriconazole, amphotericin B and anidulafungin, by concentration gradient Etest® strip technique. Results: Out of 988 swabs, 355 isolates were identified as Candida species from 232 patients, being 89 isolates retrieved from patients that remained colonised at D5 and D8. AFST was conducted for all Candida isolates. The overall rate of resistance to fluconazole was 2.7%, with 3 out of 133 C. albicans, 2 out of 89 C. parapsilosis and 2 out of 24 C. glabrata isolates identified as resistant. Voriconazole susceptibility was observed in 99.2% of the isolates, with only one C. albicans isolate identified as resistant to this triazole. All isolates were susceptible to amphotericin B and 98.5% to anidulafungin. Three Candida spp. exhibited resistance to anidulafungin, C. albicans, C. tropicalis, and C. parapsilosis. Conclusions: This study highlights the importance of C. albicans as a frequent coloniser and showed that antifungal resistance remains uncommon among Candida isolates from ICUs in Portugal. The results may contribute to better management within institutions to guide therapeutic decision making.